Antifibrotic effect of mitomycin‐C on human vocal cord fibroblasts. (7th January 2019) - Szabó, Diána; Kovács, Dávid; Endrész, Valéria; Igaz, Nóra; Jenovai, Kitti; Spengler, Gabriella; Tiszlavicz, László; Molnár, József; Burián, Katalin; Kiricsi, Mónika; Rovó, László
Abstract : Objective: Acquired laryngotracheal stenosis is a potentially life‐threatening situation and a very difficult and challenging problem in laryngology. Therefore, new trends and innovative approaches based on antifibrotic drugs and minimally invasive regimens are being developed to attenuate laryngotracheal fibrosis and scarring. The purpose of this study was to examine the efficacy of mitomycin‐C (MMC) to reverse the transforming growth factor (TGF)‐β‐induced differentiation of MRC‐5 fibroblast and human primary vocal cord fibroblasts to reveal the possible applicability of MMC to laryngotracheal fibrotic conditions. Methods: Human primary fibroblast cells were isolated from vocal cord specimens of patients undergoing total laryngectomy. The established primary vocal cord fibroblast cell cultures as well as the MRC‐5 human fibroblast cells were treated with 5 ng/mL TGF‐β alone and then with 0.5 µg/mL MMC for 24 hours. Differentiation of fibroblasts was characterized by α‐smooth muscle actin (α‐SMA) immunhistochemistry, Western blot analysis, and real‐time polymerase chain reaction. Cell motility was assessed by wound‐healing assay. Results: Elevated α‐SMA mRNA and protein expression as well as increased cell motility were observed upon TGF‐β exposures. However, after MMC treatments the TGF‐β‐induced fibroblasts exhibited a significant decrease in α‐SMA expression and wound‐healing activity. Therefore, TGF‐β‐stimulated fibroblast‐myofibroblast transformation was reversed at least in part by MMC treatment. Histopathological examinations of tissue specimens of a laryngotracheal stenosis patient supported these findings. Conclusion: Antifibrotic effects of MMC were demonstrated on the human MRC‐5 cell line and on primary vocal cord fibroblast cultures. These results verify that MMC can be used with success to reverse upper airway stenosis by reverting the myofibroblast phenotype. Level of Evidence: NA Laryngoscope, 129:E255–E262, 2019